Montagem dos genomas da cultura não-axênica de nostoc sp. CACIAM 19 utilizando técnicas de metagenômica - GARCIA, Ariane Elizabeth Nunes (2020)
Bioinformatics consists of the computational study that can obtain, organize and analyze biological information from the knowledge of sequences of biomolecules. It is a new science that has roots in computer science, statistics and molecular biology. It was developed to organize the results obtained in gene sequencing, which are increasingly improving and producing increasing amounts of sequence data. With the technological advancement of genomic sequencing platforms, it becomes possible to significantly increase the processing of thousands of DNA bases in a single run, reducing costs and speeding up the sequencing speed. This technological advance also makes it possible to obtain knowledge from biological data taken directly from a microbial community, characterizing metagenomic studies. Metagenomic techniques consist of DNA extraction, sequencing, assembling, separation and classification of genomes. Along with technological advancement of the sequencers have come new assembly approaches that are capable of processing a large scale of data with high coverage. In this work, we aimed to assemble the genomes present in the non-axenic cyanobacteria culture sample Nostoc sp. CACIAM 19, using metagenomic approaches. As results, genomes of six genera were separated and classified in the sample, with the presence of the cyanobacteria genome in smaller abundance.